2020
DOI: 10.1101/2020.04.13.040063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter fascicles and cortical microstructure predict reading-related responses in human ventral temporal cortex

Abstract: HighlightsThe ILF, AF and VOF predict the spatial layout of reading-related responses in VTC Gray matter microstructure improves the prediction of reading-related responses Fascicles and gray matter structure together predict the location of the VWFA Abstract Reading-related responses in the lateral ventral temporal cortex (VTC) show a consistent spatial layout across individuals, which is puzzling, since reading skills are acquired during childhood. Here, we tested the hypothesis that white matter fascicles a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Constraints imposed by connectivity in the brain may also limit what neural populations language regions can read-out from, making the learning process more difficult. The visual word form area exhibits preferential functional and structural connectivity with language regions of the brain (Stevens et al, 2017; Yeatman et al, 2013), and its location can be predicted based on measurements of structural connectivity (Grotheer et al, 2021; Saygin et al, 2016). These connectivity constraints may prevent the learning of read-out mechanisms operating over the entire population code of inferotemporal cortex, instead requiring read-out from the visual word form area (Hannagan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Constraints imposed by connectivity in the brain may also limit what neural populations language regions can read-out from, making the learning process more difficult. The visual word form area exhibits preferential functional and structural connectivity with language regions of the brain (Stevens et al, 2017; Yeatman et al, 2013), and its location can be predicted based on measurements of structural connectivity (Grotheer et al, 2021; Saygin et al, 2016). These connectivity constraints may prevent the learning of read-out mechanisms operating over the entire population code of inferotemporal cortex, instead requiring read-out from the visual word form area (Hannagan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This process gave us the functionally defined white matter fascicles for each functional ROI. Previous work showed that out of those fascicles classified by AFQ, only 5 fascicles connect to VTC: the inferior longitudinal fasciculus (ILF), inferior frontal occipital fasciculus (IFOF), arcuate fasciculus (AF), posterior arcuate fasciculus (pAF), and vertical occipital fasciculus (VOF) (Ben-Shachar et al 2007;Thomas et al 2009;Wandell and Yeatman 2013;Yeatman et al 2013;Tavor et al 2014;Gomez et al 2015;Song et al 2015;Weiner et al 2016;Kay and Yeatman 2017;Lerma-Usabiaga et al 2018;Broce et al 2019;Grotheer et al 2019;Grotheer, Yeatman, et al 2021). To determine the fascicle connectivity profile, we calculated the distribution of its connections across these five fascicles for each functional ROI in each subject.…”
Section: Connectivity Profiles Of Functionally Defined White Mattermentioning
confidence: 99%
“…We first examined the fascicle connectivity profiles of VTC face-and wordselective regions in each individual's brain. There are five fascicles that connect to visual regions in VTC (Ben-Shachar et al 2007;Thomas et al 2009;Wandell and Yeatman 2013;Yeatman et al 2013;Tavor et al 2014;Gomez et al 2015;Song et al 2015;Weiner et al 2016;Kay and Yeatman 2017;Lerma-Usabiaga et al 2018;Broce et al 2019;Grotheer et al 2019;Grotheer, Yeatman, et al 2021) (Catani et al 2002), which connects the occipital lobe and frontal lobe, the inferior longitudinal fasciculus (ILF) (Catani et al 2002), which connects the occipital lobe and ventral temporal lobe, the arcuate fasciculus (AF) (Catani et al 2002), which connects the ventral temporal lobe and the frontal lobe, the posterior arcuate fasciculus (pAF) (Weiner, Yeatman, et al 2017), which connects the ventral temporal lobe and the parietal lobe, and the vertical occipital fasciculus (VOF) (Yeatman, Weiner, et al 2014;Takemura et al 2016;Weiner, Yeatman, et al 2017), which connects the ventral and dorsal occipital lobe. Therefore, our fascicle connectivity analysis will focus on these five fascicles.…”
Section: Fascicle Connectivity Profiles Of Vtc Functional Rois Are Or...mentioning
confidence: 99%
See 2 more Smart Citations